Enhancement of thermal conductivity for epoxy laminated composites by constructing hetero‐structured GF/BN networks. Issue 1 (17th October 2022) - Li, Chenglin; Du, Qingyuan; Liu, Changhao; An, Yi; Liu, Ying; Zheng, Xiuting; Ru, Yue; Gao, Dali; Wu, Daming; Sun, Jingyao
Abstract: Due to the rapid development of multifunctional and miniaturized electronic devices, the demand for polymer composites with mechanical properties, high‐thermal conductivity, and dielectric properties is increasing. Therefore, the heat dissipation capacity of the composite must be improved. To solve this problem, we report a glass fabric (GF)/boron nitride (BN) network with a highly thermally conductive hetero‐structured formed using polyvinyl alcohol (PVA) as an adhesive. The GF and BN are furtherly modified by (3‐aminopropyl)triethoxysilane (APTES) for better thermal conductivity enhancement. When the BN content is 30%, the thermal diffusion coefficient and thermal conductivity of obtained PVA‐mBN@mGF (PBG) are 2.843 mm 2 /s and 1.394 W/(m K), respectively. Epoxy (EP) resin is then introduced to prepare PBG/mBN/EP laminated composites via the hot pressing method as applied as thermal conductive composites. A highest thermal conductivity of 0.67 W/(m K) of PBG/mBN/EP laminated composites is obtained, three times higher than that of pure EP. In addition, the PBG/mBN/EP laminated composites also present favorable mechanical, electrically insulating, and dielectric properties. Abstract :